(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This work investigated the impact of acidified turmeric on growth, blood profile, and gut bacterial counts of broiler chickens stocked in an overcrowding stress condition. Materials and Methods: A total of 285 14-day-old Lohmann broiler strains were distributed to T0 (chicks receiving basal feed raised at a density of 9 chicks/m2 ), T1 (chicks receiving basal feed raised at 16 chicks/m2 ), T2 (chicks receiving 1% turmeric powder raised at 16 chicks/m2 ), and T3 (chicks receiving 1% acidified turmeric powder raised at 16 chicks/m2 ). Body weight and feed intake were determined weekly. On day 37, blood and intestinal content were collected and analyzed. Results: Body weight was higher while feed conversion ratio was lower in T0 than in other groups. Compared to T0, T1 had a lower thymus weight. Erythrocytes and hematocrits were greater in T0 than in T2 and T3. Hemoglobin was higher in T0 than in T3. Serum superoxide dismutase differed as T0 < T1 < T2. Ileal coliform was higher in T0 than in T1 and T3. Lactic acid bacteria counts were higher in T0 and T1 than in T2 and T3. Conclusions: Acidified turmeric was capable of maintaining the relative weight of the immune organ and ameliorating the oxidative stress of the broiler during overcrowding stress. J. Adv. Vet. Anim. Res., 9(1): 87–94, March 2022 http://doi.org/10.5455/javar.2022.i572